Ochratoxin A determination in beer by immunoaffinity column clean-up and high-performance liquid chromatography - Prado,Guilherme (2003)
Analyses of ochratoxin A (OTA) in domestic and imported beers were perfomed by immunoaffinity column and high - perfomance liquid chromatography (HPLC) using a fluorescence detector. Recoveries of OTA from beer samples spiked at levels from 8.0 to 800pg/mL ranged from 81.2% to 95.0%, with coefficient of variation between 0% e 11.0%. Detection limit and quantification limit were 2.0pg/mL and 8.0pg/mL, respectively. Of the total of 26 samples produced in Brazil only 6 (23%), contained trace amounts of OTA. Of the 4 imported beers, in 2, Ireland and Germany, were detected OTA at levels of 25pg/mL and 82pg/mL, respectively.